2022
DOI: 10.1111/jocn.16377
|View full text |Cite
|
Sign up to set email alerts
|

Professional competence development through interprofessional simulation‐based learning assists perioperative nurses in postgraduation acute clinical practice situations: A qualitative study

Abstract: Aims and objectives To explore recently graduated perioperative nurses' experiences of interprofessional simulation‐based learning during postgraduate education and investigate whether and how this learning approach contributed to the development of their professional competence in meeting acute clinical situations. Background Perioperative nursing requires specialised education that offers professional development to ensure high‐quality nursing care and patient safety in acute situations. Interprofessional si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…These elements can be challenging for newly graduated nurses and in wards where nurses have to care for many patients simultaneously [31]. To ensure the correct response to patient deterioration, prompt escalation can be taught using simulation training [45]. One study showed that using simulation improved nurses' ability to transfer knowledge to clinical practice and, thereby, the ability to identify deteriorating patients and enhance patient care [46][47][48].…”
Section: Gaps In Practicementioning
confidence: 99%
“…These elements can be challenging for newly graduated nurses and in wards where nurses have to care for many patients simultaneously [31]. To ensure the correct response to patient deterioration, prompt escalation can be taught using simulation training [45]. One study showed that using simulation improved nurses' ability to transfer knowledge to clinical practice and, thereby, the ability to identify deteriorating patients and enhance patient care [46][47][48].…”
Section: Gaps In Practicementioning
confidence: 99%